(untitled) (Research, Society and Development, 2022)
The Passiflora genus has a wide distribution and genetic variety that can be used in breeding and conservation programs. However, few species have been explored at the genetic and molecular level. Due to the lack of knowledge of this nature, especially for wild species, the objective was to evaluate the diversity and genetic structure in commercial and wild species of the genus Passiflora. The study consisted of analyzing the amplification profile of 17 combinations of RGA primers in 178 accessions (79 species represented by 166 accessions and 12 varieties - EMBRAPA BRS). For data analysis, the amplification products were submitted to agarose gel electrophoresis and subsequent construction of a binary data table (presence and absence of amplifications). Data were submitted to molecular variance, principal component and Bayesian analysis. The results, considering only the polymorphism between species and varieties (criterion I, adopted in this study) showed seven combinations of RGA primers with relevant numbers of loci presence. When considering all accessions (criterion II, adopted in this study), the 17 combinations of RGA resulted in 100% polymorphic marks. The Bayesian analysis indicated two possibilities of structuring, with k=2 being the most likely structuring and K=5 an alternative, less likely sub-structuring. In the analysis of molecular variance, greater diversity was observed between subgenera and varieties, indicating low genetic structuring between accessions. The main coordinate analysis, on the other hand, showed a wide distribution of accessions representative of the species and greater structuring between these accessions and the varieties. The 17 RGA primers were efficient for genetic characterizations of Passiflora spp.